PENGARUH PERPUTARAN MODAL KERJA DAN DER TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2013 – 2016 - Aldin Azura, 14.05.52.0140; Susilowati, Yeye (Students' Journal of Accounting and Banking, 2018)
This study is a research that examines and analyzes the effect of cash turnover, receivable turnover, inventory turnover and debt equity of ratio (DER) on the profitability of companies listed on the Indonesia Stock Exchange 2013-2014. This study uses purposive sampling method in sample selection, with sample criteria is a company listed in Indonesia Stock Exchange during the period 2013-2016. Based on these criteria, obtained sample of 244 to 141 companies during the four-year observation period. The relationship and / or influence between variables are explained by using multiple linear regression analysis method. The results showed that cash turnover had a significant negative effect on profitability (ROA). Positive receivable turnover has no effect on profitability (ROA). The positive inventory turnover has no effect on profitability (ROA). DER (debt to equity ratio) has a significant negative effect on profitability (ROA). Keywords: Profitability (ROA), Cash Turnover, Receivable Turnover, Inventory Turnover, and Debt to Equity Ratio (DER).